From Structure to Social Dimensions: A Contrastive Study on Numerical Systems in Indonesian, Javanese, and Balinese - Wijana, I Dewa Putu; Yoga, Adwidya (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The study of numerical systems in Indonesian, Javanese, and Balinese languages reveals significant syntactic and semantic differences despite their genetic relation within the Austronesian family. This paper examines how each language expresses numerals, categorizing them into cardinal, ordinal, collective, and indefinite types, and how these categories reflect broader sociocultural influences on linguistic development. Alwi et al. (2010) and Keraf (1991) emphasize the multifaceted roles of numbers in language, illustrating their grammatical functions and contextual nuances. This research highlights the interaction between numerals and unit nouns, enhancing the semantic richness of numerical expressions. An analysis of Balinese showcases complex categorization and phonological rules governing number formation, further complicating the learning process. In contrast, the Javanese adopt a simplified framework that may overlook certain linguistic intricacies. This comparative study explores the sociocultural dimensions that shape numerical expressions, offering insights into the interplay between language and culture in the representation of numbers. This research also implies that, in pedagogical and educational contexts, a cross-cultural understanding of numerical systems across various traditional languages in Indonesia is urgently needed to provide a cohesive teaching environment that connects subjects such as languages, math, physics, and others that involve numerical systems and terms. Abstrak Kajian tentang sistem bilangan dalam bahasa Indonesia, Jawa, dan Bali mengungkap adanya perbedaan sintaktis dan semantis yang signifikan, walaupun ketiganya secara genetis berkerabat dalam rumpun bahasa Austronesia. Artikel ini membahas bagaimana setiap bahasa mengekspresikan bilangan dengan mengategorikannya ke dalam jenis bilangan kardinal, ordinal, kolektif, dan tak tentu, serta bagaimana kategori-kategori tersebut mencerminkan pengaruh sosial budaya yang lebih luas terhadap perkembangan bahasa. Alwi et al. (2010) dan Keraf (1991) menekankan peran multifaset bilangan dalam bahasa, menunjukkan fungsi gramatikal dan nuansa kontekstualnya. Penelitian ini menyoroti interaksi antara bilangan dan kata satuan yang memperkaya makna dalam ungkapan numerik. Analisis terhadap bahasa Bali memperlihatkan kategorisasi yang kompleks serta aturan fonologis yang mengatur pembentukan bilangan, yang semakin memperumit proses pembelajaran. Sebaliknya, bahasa Jawa mengadopsi kerangka yang lebih sederhana yang berpotensi mengabaikan beberapa kerumitan linguistik tertentu. Studi komparatif ini mengeksplorasi dimensi sosial budaya yang membentuk ekspresi numerik, menawarkan wawasan tentang keterhubungan antara bahasa dan budaya dalam representasi bilangan. Penelitian ini juga mengisyaratkan bahwa dalam konteks pedagogis dan pendidikan, pemahaman lintas budaya mengenai sistem bilangan dalam berbagai bahasa daerah di Indonesia sangat diperlukan untuk menghadirkan lingkungan pembelajaran yang koheren dan menghubungkan mata pelajaran seperti bahasa, matematika, fisika, dan disiplin lain yang melibatkan sistem dan istilah bilangan.